Self-fashioning in and through language: implications for Critical Discourse Analysis - Rajagopalan, Kanavillil (Cadernos de Linguagem e Sociedade, 2010)
Critical Discourse Analysis, the way I see it, is predicated upon the premise that discourse is not merely about a language-external reality, but is a means of critically intervening in that very reality. A major challenge to the interventionist thesis is the idea of “selffashioning”, enthusiastically endorsed by contemporary neo-progmatists for whom all talk of language impinging on reality is useless philosophical golbbledygook. The pragmatist rejection of language as representation leaves no room for any critical intervention. The question I would like to pose is: Is there anything in the notion of self-fashionning that can still be salvaged and grafted on to the project of CDA ?